CAUSES OF TOOTH DECAY AND PREVENTION - Mamasoliyeva Mubina Ibrokhim qizi (Web of Journals Publishing, 2025)
Dental caries is one of the most common diseases in the human body. This disease not only causes aesthetic problems, but also has a serious impact on human health. Dental caries is a process of decay of organic and inorganic parts of tooth tissues, mainly enamel and dentin, which first forms small spots on the tooth surface, and then cavities. A thorough study of the mechanism of the onset and development of the caries process, as well as methods of its prevention, is of great importance for general health. This article aims to comprehensively cover the main causes of the development of dental caries, its pathogenesis and effective ways of prevention.